A unified Approach to Studying Engineering Infrastructure of Medical Diagnostics Centers of Uzbekistan - Ataniyazova, Raushan; Kamilova, Roza; Salomova, Feruza; Sadullayeva, Hosiyat; Sherkuzieva, Guzal (International Journal of Psychosocial Rehabilitation, 2020)
A comprehensive assessment of hygienic conditions and the state of the engineering infrastructure of the Medical Diagnostics Centers in conjunction with the impact of their activities on the formation of risk factors for environmental pollution. It is established that the unified approach, taking into account a complex of quantitative and qualitative environmental and hygienic criteria, allows to create a conceptual model of objective assessment of hygienic bases of medical care quality.